Training in-service teachers: study of questions and the organization of teaching Formation des enseignants en service: étude des questions et organisation de l'enseignement - Otero, Maria Rita; Llanos, Viviana Carolina; Parra, Veronica (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2020)
Abstract We analyse the study and research carried out by N = 31 teachers in service during an on-line course in Didactics of Mathematics, about a question that could generate a Study and research path (SRP). The teachers studied the question individually and in groups. Then, they had to organize a possible teaching, adapted to an institution well known to them .The written texts produced by the teachers are analysed by means of two types of techniques: one qualitative and one based on lexicometric statistical methods. In the long term, the aim of this research is to understand the potential and difficulties of in-service teachers to organize teaching based on questions. Keywords: Teachers training; Study and research paths Résumé Nous analysons l'étude et la recherche menées par N = 31 enseignants en service lors d'un cours en ligne sur la didactique des mathématiques, autour d'une question qui pourrait générer un PER. Les enseignants étudient la question individuellement et en groupe, puis il est proposé d'organiser un possible enseignement adapté à une institution bien connue par les enseignants, sur la base de la question étudiée. Les textes écrits produits par les enseignants sont analysés en utilisant deux types de techniques: une qualitative et l'autre basée sur des méthodes statistiques lexico métriques. Dans le long terme, cette recherche essaie de comprendre le potentiel et les difficultés des enseignants pendant l'organisation d'un enseignement basé sur des questions. Mots clés: Formation des enseignants; Parcours d'études et de recherche.